2005
DOI: 10.1039/b415098h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the photodetachment spectrum of the methylene amidogene anion (H2CN)

Abstract: The excited states of methylene amidogen (H2CN) have recently been studied extensively both by experiment and theory. However, the assignment of absorption spectra is in disagreement with the theoretical analysis. In the present study a theoretical photoelectron detachment spectrum is predicted which shows that a corresponding experiment could be suitable to decide whether the theoretical or the experimental assignment is correct. To this end, the electron affinity of H2CN was calculated very accurately. Verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…8 We also make a detailed comparison of the experimental spectra with rotational contours computed with rotational constants obtained by averaging over the b 1 umbrella motion on the ground and excited-state potential energy surfaces. 16 The experimental and simulated spectra agree extremely well with each other for an assumed type-B transition, appropriate to a 2 A 1 r 2 B 2 transition, and disagree significantly if the transition moment is assumed to lie along the a or c inertial axes. This provides strong confirmation for the 2 A 1 r 2 B 2 assignment made previously by Eisfeld.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…8 We also make a detailed comparison of the experimental spectra with rotational contours computed with rotational constants obtained by averaging over the b 1 umbrella motion on the ground and excited-state potential energy surfaces. 16 The experimental and simulated spectra agree extremely well with each other for an assumed type-B transition, appropriate to a 2 A 1 r 2 B 2 transition, and disagree significantly if the transition moment is assumed to lie along the a or c inertial axes. This provides strong confirmation for the 2 A 1 r 2 B 2 assignment made previously by Eisfeld.…”
Section: Introductionmentioning
confidence: 69%
“…Prior to the recent theoretical study by Eisfeld, 16 the consensus was that the observed electronic transition in H 2 CN was due to a dipole-forbidden but vibronically-allowed transition to the à 2 B 1 state. The experimental evidence for this assignment comes from the H atom photofragment study of Davis and co-workers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both Bernad et al [13] and Nizamov et al [14] assigned their observed absorption bands to a vibronically allowed 1 2 B 1 ← X 2 B 2 transition. Subsequently, Eisfeld and co-workers [15][16][17] carried out a series of theoretical and experimental studies of the electronic states of H 2 CN and assigned the observed electronic transition as the dipole-allowed 1 2 A 1 ←X 2 B 2 transition.…”
Section: Introductionmentioning
confidence: 99%
“…Cowles et al [18] measured the ultraviolet photoelectron spectra of H 2 CN − and * Corresponding author: wangkd@htu.cn deduced the adiabatic electron affinity of the H 2 CN molecule to be 0.511 ± 0.008 eV. Eisfeld [16] calculated the adiabatic electron affinity of 0.5152 eV calculated with zero-point energy correction. The rotational constants of H 2 CN were determined to be 9.4844, 1.3062, and 1.1423 cm −1 by the microwave spectroscopy [19].…”
Section: Introductionmentioning
confidence: 99%